Key strategies to improve systems for managing patient complaints within health facilities – what can we learn from the existing literature?. Issue 1 (1st January 2018) - Mirzoev, Tolib; Kane, Sumit
ABSTRACT: Background : Information from patient complaints – a widely accepted measure of patient satisfaction with services – can inform improvements in service quality, and contribute towards overall health systems performance. While analyses of data from patient complaints received much emphasis, there is limited published literature on key interventions to improve complaint management systems. Objectives : The objectives are two-fold: first, to synthesise existing evidence and provide practical options to inform future policy and practice and, second, to identify key outstanding gaps in the existing literature to inform agenda for future research. Methods : We report results of review of the existing literature. Peer-reviewed published literature was searched in OVID Medline, OVID Global Health and PubMed. In addition, relevant citations from the reviewed articles were followed up, and we also report grey literature from the UK and the Netherlands. Results : Effective interventions can improve collection of complaints (e.g. establishing easy-to-use channels and raising patients' awareness of these), analysis of complaint data (e.g. creating structures and spaces for analysis and learning from complaints data), and subsequent action (e.g. timely feedback to complainants and integrating learning from complaints into service quality improvement). No one single measure can be sufficient, and any intervention to improve patient complaint management system must include different components, which need to be feasible, effective, scalable, and sustainable within local context. Conclusions : Effective interventions to strengthen patient complaints systems need to be: comprehensive, integrated within existing systems, context-specific and cognizant of the information asymmetry and the unequal power relations between the key actors. Four gaps in the published literature represent an agenda for future research: limited understanding of contexts of effective interventions, absence of system-wide approaches, lack of evidence from low- and middle-income countries and absence of focused empirical assessments of behaviour of staff who manage patient complaints.